IMPLEMENTASI KEBIJAKAN PENETAPAN TARIF ANGKUTAN UMUM ANTAR KOTA DI PROVINSI SULAWESI UTARA - POLLA, VIRGINIA ANGGRIANI FELANITA; TAMPI, GUSTAAF BUDI; LONDA, VERY (Sam Ratulangi University, 2018)
Research that has been conducted aims to analyze how the Implementation of Policy Determination of InterCity Public Transportation Tariff in North Sulawesi Province. The method used in this research is qualitativemethod. Based on the results of the study can be concluded that the Implementation of the PolicyDetermination of Inter-City Public Transportation Tariff in North Sulawesi Province has not been runningproperly. Judging from the survey results in the field based on the amount of tariff written in the Decreeissued by the Governor of North Sulawesi. In the actual tariff rules on the route Kawangkoan - Manado tariffas per SK Rp 12.600, - in fact the current tariff of Rp 15.000, - route Manado - Langoan Rp 15.000, - to Rp17.000, - Manado - Tondano route Rp 9,400, - to Rp 10,000, - Manado - Tomohon route Rp 7, 400, - to Rp8.000, - Manado - Kotamobagu route Rp 34.500 to Rp 55.000, - Manado - Bitung route Rp 9,700, - to Rp10.000, - and route Manado - Amurang Rp 13.800, - to Rp 15.000 , -.The sanctions stated in Article 10 in thePergub of North Sulawesi number 13 of 2016 which should be feared by the recipients of policies that violatethe rules are in fact not known by the recipients of the policy so that it becomes something that is consideredunimportant to something that is not important to be conveyed and known. Furthermore, four factors thatdetermine the success of a policy implementation of communication, resources, disposition, bureaucraticstructure has not been implemented and a barrier to the successful implementation of the policy ofdetermining public transportation rates. Lack of public respect for existing policies for various reasons thatexist inhibit the implementation of a policy. To solve the existing problems in the implementation of the intercity public tariff policy adoption in North Sulawesi Province, provincial and district / city governments aspolicy makers and policy-makers should be concerned about whether or not a policy should be implemented.Keywords: Policy Implementation, Public Transportation, Tariff.